Speaking Anxiety Viewed from Krashen’s Affective Filter Hypothesis During Seminar Proposal Presentation - K. Dedy Sandiarsa S.; Ahmad Hanan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Speaking anxiety remains a common issue experienced by students learning English as a Foreign Language (EFL), especially when they are required to perform in formal academic presentations. This study investigated the factors contributing to speaking anxiety among final-semester students during seminar proposal presentations and examined how the anxiety influenced their ability to present and respond to examiners’ questions from the perspective of Krashen’s Affective Filter Hypothesis. The study employed a qualitative case study design involving 15 students of the English Education Study Program, Faculty of Culture, Management, and Business (FBMB), Universitas Pendidikan Mandalika. Data were collected through classroom observations, semi-structured interviews, and supporting documentation. The collected data were analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results showed that students’ anxiety was influenced by three major aspects: psychological, linguistic, and situational factors. Psychological aspects such as fear of making mistakes, nervousness, and low self-confidence appeared to be the strongest contributors. In addition, limited vocabulary, concerns about grammar, pronunciation difficulties, and pressure during question-and-answer sessions also increased students’ anxiety levels. The study further found that anxiety affected students’ fluency, concentration, confidence, and ability to explain ideas clearly during presentations. Many students experienced hesitation, difficulty organizing explanations, and problems responding spontaneously to examiners’ questions. Viewed from Krashen’s Affective Filter Hypothesis, these findings indicate that high anxiety can function as an emotional barrier that disrupts students’ speaking performance in academic settings. This study highlights the importance of creating supportive learning environments and providing more opportunities for academic speaking practice to help students reduce anxiety and improve presentation performance.